Norrskensturism utan norrsken : Gästförväntningar och alternativa upplevelser - Eshima, Naoko (2015)
Today, we use the word ”experience” frequently. We live in an experience society where the most attractive economic offering is experiences. Tourism is one part of the experience economy where tourists expect memorable experiences. In the Northern part of Nordic countries, Northern lights tourism has boomed up during the last decades. But Northern lights are natural phenomena. You cannot control them. There is no guarantee to see them. This thesis have therefore purpose to study how an extraordinary experience would be offered with help of experience production perspectives. Areal limitation of the study has been Kiruna Lapland in Northern Sweden. Study showed that the visitors of Kiruna Lapland mostly expect to see Northern light. Thus, most of the northern lights tour providers have no other plan for bad weather- and/or solar conditions. Since we human beings cannot control the natural phenomena, the tour providers should be prepared with alternative experiences for the guests. These should be unexpected experiences that bring the experience into the mind. In addition, they should engage the guests in active way, since Northern light tours tend to be a passive aesthetical experience. Validerat; 20150701 (global_studentproject_submitter)